A New Dawn for Brazilian Pediatric Cardiac Surgery Is on the Way - Issues Around and Outside the Operating Room - Caneo,Luiz Fernando (2022)
ABSTRACT In some developing countries, congenital heart disease still stands out among the leading causes of death in the first year of life. Therefore, there is a great need to develop programs designed to improve outcomes in the diagnosis and surgical treatment of congenital heart disease in these nations, where children have always been and still are severely underserved. The Brazilian Public Health Care System demands universal access to treatment as a constitutional right. Therefore, an underfunded Pediatric Cardiac Surgery program is unacceptable since it will cost lives and increase the infant mortality rate. Additionally, poor funding decreases providers’ interest, impedes technological advances and multidisciplinary engagement, and reduces access to comprehensive care. Unfortunately, in most developing countries, Pediatric Cardiac Surgery progress is still the result of isolated personal efforts, dedication, and individual resilience. This article aims to present the current state of Brazilian pediatric cardiac surgery and discuss the structural and human limitations in developing a quality care system for children with congenital heart disease. Considering such constraints, quality improvement programs via International collaboration with centers of excellence, based on proper data collection and outcomes analysis, have been introduced in the country. Such initiatives should bring a new dawn to Brazilian Pediatric Cardiac Surgery.